(untitled) (mathematica didactica, 2002)
Since TIMMS/III-Germany the mathematics education in upper secondary level course has come under criticism. Especially the fundamental level course needs improvement. The discontent with analytic geometry at school is evident. By working out the example of Bézier curves, a visionary view of an integrative fundamental level course concept will be presented, emphasising the mathematical literacy education considering the psychology of metacognition. The workouts out of pupils give an insight into the realization of this concept.